A Python program to merge Sanger sequences: an update - Lin, Shiming; Huang, Bifang; Zhao, Li-li; Xu, Fei; Pan, Danni; Chen, Xuanyang; Lin, Shiqiang (PeerJ (San Francisco, CA), 2024)
Gene cloning is an important step in investigating gene structure and function. To verify gene sequence, Sanger sequencing is used, which may produce several overlapping sequencing files that need to be merged before alignment to the target gene sequence is performed. Previously, we reported the Python program to Merge Sanger sequences ( https://peerj.com/articles/11354/ ), which ran in command line and relied heavily on EMBOSS suite. In this updated version of the program, we have made several remarkable improvements. It provides a graphical user interface (GUI) written with tkinter, which is convenient and stable. It does not require users to rename the input sequences before performing merging. With regard to the implementation, the updated version utilizes Python function (Align.PairwiseAligner) to align adjacent sequences, which is more flexible (can adjust program parameter i.e. , the number of first-time consecutive matching bases). The new version of the program makes merging Sanger sequences much more convenient and facilitates gene study.